Fiber Lasers. Issue 2 (April 2014) - Hartinger, Klaus; Holzwarth, Ronald
Abstract Fiber lasers in general are receiving increased attention for industrial applications and have captured their share next to gas and solid‐state lasers. As a company, we focus on the research of femtosecond fiber technology and the development of laser products which rely on quality, reliability, cost efficiency and versatility. Our customers apply our femtosecond fiber lasers for purposes varying from high precision spectroscopy, to THz generation for quality inspection, to micro‐material processing. Here we will focus on femtosecond fiber lasers and some of the breakthrough developments and progress they have allowed in science and industry.